Narrative and Characterization Techniques in Sue Monk Kidd’s Novel The Secret Life of Bees (An Analysis with Narratological Approach) - Anya Pritafania (Universitas Pendidikan Indonesia (UPI), 2014)
The present study is aimed at investigating the type of Indonesian cultural words found in the novel Negeri 5 Menara and the translated novel, and also to examine the translation techniques used by the translator in translating them into English, the translator’s tendency in translating cultural words and the factors leading to the translator’s tendency. To analyze the kinds of cultural word found in the novel and how those cultural words are translated, three primary theories were used: cultural words classification (Newmark, 1988), translation techniques (Molina Albir, 2002), and translation strategies (Venuti, 2004). To investigate factors leading to the translator’s tendency the interview with the translator was held. The result of the study shows that there are various kinds of cultural word found in the novel and most of them were domesticated. The factors leading to the translator’s tendency were cultural differences and the author’s intention to get wider readership. Keywords: Narrative techniques, Barry’s Version (2002) of Genette’s narratology theory (1980), Narrative Categorizations, Characterization, Methods of Characterization